1999
DOI: 10.1590/s0034-71081999000200005
|View full text |Cite
|
Sign up to set email alerts
|

Periwinkle (Gastropoda: Littorinidae) habitat selection and its impact upon microalgal populations

Abstract: The present study examines habitat selection and grazing pressure of the periwinkle Nodilittorina lineolata (Gmelin, 1791) on the rocky shore of Arraial do Cabo, RJ, Brazil (lat. 23°S, long. 43°W). Transfer experiments suggest that periwinkles actively select the mid intertidal, where the cirripede Chthamalus bisinuatus Pilsbry is the dominant sessile invertebrate. We also conducted a caging experiment in the middle intertidal, manipulating grazers and light, to assess the impact of grazing upon microalgal den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Although there are studies on the role of biofilm as an important component in intertidal systems around the world (e.g. Australia : Underwood 1984a,b, MacLulich 1986, 1987, Jackson et al 2010; South Africa: Dye & White 1991, Kaehler & Froneman 2002Europe: Hill & Hawkins 1991, Thompson et al 2004North America: Nicotri 1977;Hong Kong: Nagarkar et al 2004, Nagarkar & Williams 1997, 1999, Williams 1994, Williams et al 2000, it is an almost unresearched assemblage on rocky shores in the southwest Atlantic (but see Apolinario et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies on the role of biofilm as an important component in intertidal systems around the world (e.g. Australia : Underwood 1984a,b, MacLulich 1986, 1987, Jackson et al 2010; South Africa: Dye & White 1991, Kaehler & Froneman 2002Europe: Hill & Hawkins 1991, Thompson et al 2004North America: Nicotri 1977;Hong Kong: Nagarkar et al 2004, Nagarkar & Williams 1997, 1999, Williams 1994, Williams et al 2000, it is an almost unresearched assemblage on rocky shores in the southwest Atlantic (but see Apolinario et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The grazer L. ziczac appeared amongst the cirripedes but not as abundant as on the littoral fringe, which was usually called "Littorinid zone". However, Apolinário et al (1999) observed that littorinids were much more abundant in the middle-intertidal zone aggregating amongst cirripedes. The grazing limpet Collisella subrugosa, commonly found in this zone, was also mentioned as an abundant archiogastropod in the Brazilian coast, occurring from the tropical northeast up to the subtropical southeast coast (Rios, 1995apud Tanaka, 2001.…”
Section: Discussionmentioning
confidence: 96%
“…This band was characterized by a higher coverage of grazing gastropods, Littorina spp, which were also found over a large extension in the Western Atlantic (Coelho et al, 2004). The ecological importance of these grazers is related to the control of microalgal populations (Apolinário et al, 1999). Aggregation, selection of habitat, decreasing shell pigmentation and increased/decreased shell ornamentation are some adaptations of Littorina to survive in this harsh environment where the desiccation stress is the highest (Chapman and Underwood, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latitude, in association with other factors, can directly influence the size of the gastropods (Linse et al, 2006). These factors may include body temperature (Chapperon et al, 2013;Seuront & Ng, 2016), food availability (Apolinário et al, 1999), density-dependent intraspecific competition (Magalhães, 1998) and phenotypic plasticity (Hollander et al, 2006). According to Bernardino et al (2015), the extreme conditions of El Niño, combined with long-term global warming, can lead to thermal stress on benthic assemblages found in the mid-latitudes of the tropics, and short-term osmotic stress of those organisms found in the estuaries of south-eastern Brazil.…”
Section: Discussionmentioning
confidence: 99%